EKSPLORASI DAN IDENTIFIKASI PURUN DANAU (Lepironia articulata) LOKAL SEBAGAI ADSORBEN ALAMI PADA IKLIM TROPIKA LEMBAB DI KALIMANTAN TIMUR - Donny Dhonanto; Agung Enggal Nugroho; Apdila Safitri; Khoiru Indana; Odit Ferry Kurniadinata; Penny Pujowati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Purun is one of the endemic plants that naturally grows wild in peat and swamp areas. Purun is commonly found in peat and swamp areas in Indonesia, including in East Kalimantan, especially in Kabupaten Kutai Kertanegara. Purun belongs to the Cyperaceae family. This plant is a typical plant in swamp land. Swamp land is land for a long time during the year is always saturated with water or inundated. Purun is a plant that lives in the wild naturally in areas of peat swamp, tidal swamp and river areas that are acidic sulphate.There are three types of purun known in Kalimantan, namely purun danau, purun tikus and purun bajang. The purun danau (Lepironia articulata Retz. Domin.) has a fundamental difference when compared to the purun tikus and the purun bajang, which is much larger in size than the purun tikus and the purun bajang and has leaves that are tougher like woody and more clearly lined than other. Purun danau also has a cavity that is similar to a bamboo stick. The objectives of the study were to 1. determine the character of purun danau plants in the natural humid tropics habitat; and 2. Knowing the characteristics of purun danau plant habitat. The research design used in this research is descriptive or descriptive research. The results showed that: 1. the morphological character of the purun danau was in the form of a cylindrical stem like a pipe that grew elongated with a tapered tip, had thin partitions that filled the inside, the bulkhead was solid at the base and the stem was shiny green. The outer part of the base is white and covered with leaves shaped like a reddish brown sheath. The tapered end of the stem then grows into a compound flower which will contain many seeds in the generative phase. Purun danau flowers are compound flowers and are located at the end of the stem. The roots of purun danau are fibrous and grow with the stolons. 2. The purun danau habitat is characterized by the presence of water, either always stagnant or flowing water with varying heights (between 100 cm to 300 cm). In addition to the presence of water, purun habitat is also characterized by acidic soil pH conditions (4.10-5.20) and open land without shade. In addition to adapting well in acid sulphate soils, purun danau are also able to absorb heavy metal elements such as Pb, Cd and Zn.